From Anti Hero to Antihero : Cruella De Vil's characterization as an antagonist and a protagonist - Hyvönen, Tuuli (My University, 2024)
The topic of this thesis is the characterization of Cruella De Vil. She is both the antagonist of The Hundred and One Dalmatians (1961) and the protagonist of Cruella (2021). In this thesis, Cruella is studied both as an antagonist and as a protagonist, her characterization and how it differs between the two movies being the focal point of the thesis. The research method utilized is the qualitative method and the main materials for the research were the two Disney films: Hundred and One Dalmatians (1961) and Cruella (2021). The goal of this thesis is to see how the same character can be characterized when they’re the antagonist or the protagonist of a story, using Cruella De Vil as a specific example character, and how for example the year of publication and the target audience affect said characterization. The results show that it is difficult to characterize the same character as evil in one source material and as good in another without having to change the character and her surroundings in major ways. For example, to make Cruella likable in the 2021 movie, many of her major motivations and characteristics from the 1961 movie have been removed or changed. Cruella in both films is, as such, similar but also highly different.
Keywords: characterization, antagonist, protagonist